The Power of Workplace Spirituality in Fostering Job Satisfaction and Work Engagement - Rusdi, Muhammad; Hartono, Arif (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines the idea of the ideal workplace through the relationship between workplace spirituality and work engagement, highlighting its academic contribution by demonstrating how affective mechanisms strengthen the engagement process. The study also clarifies the mediating role of job satisfaction. Using a correlational design with data from employees of zakat institutions (n = 124), the analysis employed partial least squares. Workplace spirituality showed a positive association with work engagement, and job satisfaction was positively linked to both constructs. Mediation results confirmed that job satisfaction significantly transmitted the influence of workplace spirituality on engagement. These findings deepen understanding of how internal meaning systems shape workforce vitality and can guide managers in designing environments that enhance satisfaction and sustain engagement.